2017
DOI: 10.1038/srep44093
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of uterine rupture among women with prior caesarean section: WHO Multicountry Survey on Maternal and Newborn Health

Abstract: Caesarean section (CS) is increasing globally, and women with prior CS are at higher risk of uterine rupture in subsequent pregnancies. However, little is known about the incidence, risk factors, and outcomes of uterine rupture in women with prior CS, especially in developing countries. To investigate this, we conducted a secondary analysis of the World Health Organization Multicountry Survey on Maternal and Newborn Health, which included data on delivery from 359 facilities in 29 countries. The incidence of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
87
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 27 publications
10
87
5
Order By: Relevance
“…Although the overall repeat CD rate in the present study is similar to that observed in the WHO Multicountry Survey (79.4% vs 81.5%, respectively), the present ERCD rate is 50% higher than that reported by the WHO (66.1% vs 43.0%). The repeat CD rate in the present study is also higher than that in European countries, such as France (65%) and the Netherlands (53%) .…”
Section: Discussionsupporting
confidence: 65%
“…Although the overall repeat CD rate in the present study is similar to that observed in the WHO Multicountry Survey (79.4% vs 81.5%, respectively), the present ERCD rate is 50% higher than that reported by the WHO (66.1% vs 43.0%). The repeat CD rate in the present study is also higher than that in European countries, such as France (65%) and the Netherlands (53%) .…”
Section: Discussionsupporting
confidence: 65%
“…Systematic review of literature showed that median incidence of uterine rupture was 5.3 per 10 000 births with much higher incidence in developing countries. 11,13,14 In developed countries the incidence is less than 1 per 1000 deliveries. 15,16 Different studies in Ethiopia showed that the incidence of uterine rupture ranges from 0.3% to 2.4%.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] It is associated with significant uterine bleeding and fetal distress necessitating prompt delivery, major surgery or uterine rent. [8][9][10][11] It is an obstetric catastrophe contributing for as many as 9.3% of maternal deaths. 12 The incidence of ruptured uterus varies in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The reported incidence of uterine rupture among women with prior CS ranged from 0.2% in high human development index (HDI) countries to 1% in low HDI countries and in India the incidence is 1.69%. [8,9] Rupture of an unscarred uterus may be either traumatic or spontaneous. Traumatic factors include mid to high operative vaginal deliveries, assisted breech delivery, internal podalic version, abdominal trauma, labour induction and in particular the unmonitored usage of oxytocin or prostaglandins.…”
Section: Introductionmentioning
confidence: 99%